Material Adsorben untuk Remediasi Air: Tinjauan Literatur Berdasarkan Variabel pH, Waktu Kontak, dan Konsentrasi - Rivaldo Bintang Sitorus; Sovian Aritonang (Rekayasa Material, Manufaktur dan Energi, 2026)
Heavy metal contamination in water sources has become a growing environmental concern due to industrial, mining, and domestic waste activities. Metals such as Pb, Cd, Cr, Cu, and Fe are toxic, non-biodegradable, and tend to accumulate in living organisms. One effective method for removing heavy metals from water is adsorption, a process where metal ions adhere to the surface of solid materials. This method is favored for its efficiency, low cost, and ability to utilize natural materials. This literature review examines fifteen recent studies (2020–2025) focusing on the performance of natural and modified adsorbents derived from agricultural biomass, fishery waste, and natural minerals. The analysis emphasizes the influence of pH, contact time, and metal concentration on adsorption capacity and efficiency. The findings show that optimum conditions generally occur at pH 4–6 with contact times of 30–120 minutes, and higher metal concentrations increase adsorption capacity until surface saturation. Chitosan- and activated carbon-based materials achieved efficiencies exceeding 90%. The study highlights the potential of natural adsorbents as sustainable and eco-friendly materials for water treatment